Comparative study on fruit development and oil synthesis in two cultivars of Camellia oleifera - Fanhang Zhang; Ze Li; Junqin Zhou; Yiyang Gu; Xiaofeng Tan (BMC Plant Biology, 2021)
Abstract Background The oil-tea tree (Camellia oleifera Abel.) is a woody tree species that produces edible oil in the seed. C. oleifera oil has high nutritional value and is also an important raw material for medicine and cosmetics. In China, due to the uncertainty on maturity period and oil synthesis mechanism of many C. oleifera cultivars, growers may harvest fruits prematurely, which could not maximize fruit and oil yields. In this study, our objective was to explore the mechanism and differences of oil synthesis between two Camellia oleifera cultivars for a precise definition of the fruit ripening period and the selection of appropriate cultivars. Results The results showed that ‘Huashuo’ had smaller fruits and seeds, lower dry seed weight and lower expression levels of fatty acid biosynthesis genes in July. We could not detect the presence of oil and oil bodies in ‘Huashuo’ seeds until August, and oil and oil bodies were detected in ‘Huajin’ seeds in July. Moreover, ‘Huashuo’ seeds were not completely blackened in October with up to 60.38% of water and approximately 37.98% of oil in seed kernels whose oil content was much lower than normal mature seed kernels. The oil bodies in seed endosperm cells of ‘Huajin’ were always higher than those of ‘Huashuo’ from July to October. Conclusion Our results confirmed that C. oleifera ‘Huashuo’ fruits matured at a lower rate compared to ‘Huajin’ fruits and that ‘Huajin’ seeds entered the oil synthesis period earlier than ‘Huashuo’ seeds. Moreover, ‘Huashuo’ fruits did not mature during the Frost’s Descent period (October 23–24 each year).